DIGITAL BANK FINANCIAL PERFORMANCE ANALYSIS AT PT BANK JAGO TBK.: ECONOMIC VALUE ADDED (EVA) APPROACH - Siska, Elmira (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
PT Bank Jago Tbk. is a conventional bank that has been transformed into a digital bank. Bank Jago has grown by extensively upgrading technology by creating numerous features in the Jago application after PT Dompet Karya Anak Bangsa (Indonesian Gojek Group) acquired 22 percent of Bank Jago's shares in 2020 with funds reaching IDR 2.25 trillion. Economic value added (EVA) is a methodology developed to complement and determine the true value of business performance. This study aims to analyze whether corporate action in technology modernization provides positive economic value added to the company. The research design used in this study is a non-statistical quantitative method. The research focus is on digital banks with case studies on PT Bank Jago Tbk. Data utilized in the research is secondary data sourced from the financial statements of PT Bank Jago Tbk. 2020 – 2022. Bank Jago's performance evaluation is carried out by analyzing the economic added value created from the bank's operations. The results of the study show that in 2020, Bank Jago's operations have not been able to create economic value added, but in the following periods, namely in 2021 and 2022, after Bank Jago modernizes technology and develops digital applications, bank operations will be able to provide added economic value. Keywords: Digital Transformation Digital Bank; Financial Performance; Economic Value Added; Bank Jago